Proyecto de factibilidad para la creación de una tienda de ropa para damas de talla plus en la ciudad de Latacunga. - Broncano Condorcana, Johana Alejandra (2024)
This feasibility project was developed to identify how feasible is to create a physical store for the marketing of youth clothing for women in plus size between ages of 20 to 29 years in Latacunga city, El Salto sector. The market research methodology was quantitative approach using survey technique and a questionnaire made up of 11 questions, a population of 12,266.91 women was considered, getting a sample of 373 surveys to collect the information, three launches were carried out digitally, and 145 responses were obtained, again a second launch was sent, which one obtained 273, and finally the third launch was carried out where the number of surveys required by the sample size was obtained. To lead to the creation of this project, this survey was applied to the women area, obtaining an approximate 98% of women who support this business. Subsequently, a technical study was carried out, which details the surface size and installed capacity, on the other hand, a financial study was also carried out, which details the initial investment of 21,591.16, yielding a net present value of 62,191.29, an IRR of 26.64% in a recovery period of 2 years, 8 months and 26 days and a cost benefit of 1.53%, with these obtained results it has been possible to determine project realizable, it is also profitable, so that it would contribute positively according to the made that projection.